2016
DOI: 10.1080/01431161.2016.1190476
|View full text |Cite
|
Sign up to set email alerts
|

Deriving diurnal variations in sun-induced chlorophyll-a fluorescence in winter wheat canopies and maize leaves from ground-based hyperspectral measurements

Abstract: Remote sensing of solar-induced chlorophyll-a fluorescence (SIF) is a promising method for quantifying photosynthetic activity at the Earth's surface. Some recent studies therefore aim to clarify to what extend passive SIF measurements can be used to track photosynthetic processes. The present study contributes to that research by investigating the diurnal relationship between shortterm variability of SIF and gas exchange rates in terms of stomatal conductance (g s ). Quantification of SIF was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In general, observed diurnal trends of and for all crops followed the temporal dynamic of PAR. This is in accordance with previous studies presenting diurnal courses of SIF 760 of different plants at canopy ( Campbell et al, 2019 ; Liu et al, 2017 ) and leaf level ( Süß et al, 2016 ; Amoros-Lopez et al, 2008 ). In addition, several studies reported data ranges of ( Liu et al, 2019 ; Pinto et al, 2017 ; Rossini et al, 2015 ; Wieneke et al, 2016 ) comparable to those shown here.…”
Section: Discussionsupporting
confidence: 94%
“…In general, observed diurnal trends of and for all crops followed the temporal dynamic of PAR. This is in accordance with previous studies presenting diurnal courses of SIF 760 of different plants at canopy ( Campbell et al, 2019 ; Liu et al, 2017 ) and leaf level ( Süß et al, 2016 ; Amoros-Lopez et al, 2008 ). In addition, several studies reported data ranges of ( Liu et al, 2019 ; Pinto et al, 2017 ; Rossini et al, 2015 ; Wieneke et al, 2016 ) comparable to those shown here.…”
Section: Discussionsupporting
confidence: 94%
“…Analogous to NDVI, PRI is calculated using Equation (1), which uses reflectance at 531 nm and a reference reflectance at 570 nm that is insensitive to the xanthophyll cycle [11]. It has been demonstrated that PRI can track changes in the photosynthesis and water stress of plants at the canopy level using ground or aerial platforms [4,12,16,20].…”
Section: Introductionmentioning
confidence: 99%
“…Common SIF retrieval approaches include conventional Fraunhofer line discrimination (FLD), improved FLD variants, and reflectance-based ratios [24]. Many studies explored the use of ground based spectrometers to retrieve the SIF values of plant leaves, and reported high correlations between SIF measurements and fluorescence measured using active techniques (e.g., PAM fluorometers) [24][25][26][27]. Large national research institutions (e.g., the European Space Agency, the EPA, and the National Aeronautics and Space Administration (NASA)) launched programs to investigate the use of hyperspectral imagery sensed remotely from planes and satellites to monitor SIF changes at the regional and global levels, to estimate carbon fixation (or flux of carbon dioxide) and gross primary productivity (GPP).…”
Section: Introductionmentioning
confidence: 99%